Post-activation potentiation in propulsive force after specific swimming strength training - Barbosa, A. C.; Barroso, R.; Andries, O. (International Journal of Sports Medicine, 2016)
We investigated whether a conditioning activity (8×12.5 m with 2.5 min-interval using both hand paddles and parachute) induced post-activation potentiation in swimming propulsive force and whether a swimmer`s force level affected a post-activation potentiation response. 8 competitive swimmers (5 males and 3 females, age: 18.4±1.3 years; IPS=796±56) performed a 10?s maximum tethered swimming test 8 and 4 min before (the highest value was considered as PRE), and 2.5 and 6.5 min after (POST1 and POST2, respectively) the conditioning activity. Rate of force development was not affected, but peak force in POST1 (p=0.02) and impulse in both POST1 (p=0.007) and POST2 (p=0.004) were reduced. Possibly the conditioning activity induced greater fatigue than post-activation potentiation benefits. For instance, the number of repetitions might have been excessive, and rest intervals between the conditioning activity and POST1 and POST2 were possibly too short. There were positive correlations between PRE peak force and changes in peak force and rate of force development. Although conditioning activity was detrimental, positive correlations suggest that weaker swimmers experience a deterioration of performance more than the stronger ones. This conditioning activity is not recommended for swimmers with the current competitive level before a competitive event.